Characteristic of the Infra based Urban Architectural Space and Rethinking of the Global Society's Public Place. (2015) - Hye-Jin, Jung; Ye-Kyeong, Shin
Abstract: The goal of this study is to investigate how the global society's representing infra-based urban architectural space like airport has revealed contemporary life and the social relationship in a spatial way. In addition, through this analysis, this study attempts to rethink the changing nature of public place.The object of this research is the international hub airport architecture, gateway of the global city and symbol.Development of communication technology and transportation means enabled the society to communicate beyond locational boundary. This world is networking among cities and interaction of communities is also being replaced by networks. Spread of the traffic space amputated the existing city organization, expanded the city's boundary, and created the landscape which only observes movements. This is the process of de-territorialization, and the idea of fixed territory became an inappropriate concept in the global society. Rather than depending on the individual's social life close to the community, the trend is transforming to a concept of network membership.Airport architecture is a space where the weakness of boundary between the nation and the community of the modern social relationship "network membership" are clearly exposed. Airport architecture started in the outskirt area, compared to the urban residential area. The reason was its characteristic of simultaneously being the node of global network and connecting local areas.Furthermore, as the competition of international hub airport increased, airport industry became a macro-complex including tourism, with an equal status with the city. Thus, airport architecture became a place of mobility dominating infra-architectural space while being dominated with the logic of capital and technology.